A Scientific Approach's Impact on Students' Writing Ability - Rastiandary, Rastiandary; Latief, Hasnawati; Ilmiah, Ilmiah; Nappu, Syamsiarna (Har Press Indonesia, 2023)
This study intended to determine whether or not SMAN 3 Kulisusu students' writing skills might be improved by using a scientific approach. The research was conducted using quasi-experiments. Students in SMAN 3 Kulisusu's tenth grade made up the research sample. The samples, which included 20 students in each of the two classes (for a total of 40), were purposefully selected. A written descriptive test for pre- and post-tests was the instrument utilized to collect the data. The results showed that the experimental group's mean post-test score (34.5) was higher than the control group's mean post-test score (18.2). With a degree of freedom (df) = 38, the value of the t-test (12.5) was higher than the t-table (2.024) at the level of significance 0.05. As a result, H0 was disproved, and Ha was accepted. Based on the results, it is considered that using a scientific approach helped the tenth-grade students at SMAN 3 Kulisusu, Kab Buton Utara, improve their writing skills.